Development of methacrylate/silorane hybrid monomer system: Relationship between photopolymerization behavior and dynamic mechanical properties. Issue 5 (7th May 2015) - Song, Linyong; Ye, Qiang; Ge, Xueping; Singh, Viraj; Misra, Anil; Laurence, Jennifer S.; Berrie, Cindy L.; Spencer, Paulette
Abstract: Resin chemistries for dental composite are evolving as noted by the introduction of silorane‐based composites in 2007. This shift in the landscape from methacrylate‐based composites has fueled the quest for versatile methacrylate‐silorane adhesives. The objective of this study was to evaluate the polymerization behavior and structure/property relationships of methacrylate‐silorane hybrid systems. Amine compound ethyl‐4‐(dimethylamino) benzoate (EDMAB) or silane compound tris(trimethylsilyl) silane (TTMSS) was selected as coinitiators. The mechanical properties of the copolymer were improved significantly at low concentrations (15, 25, or 35 wt %) of silorane when EDMAB was used as coinitiator. The rubbery moduli of these experimental copolymers were increased by up to 260%, compared with that of the control (30.8 ± 1.9 MPa). Visible phase separation appeared in these formulations if the silorane concentrations in the formulations were 50–75 wt %. The use of TTMSS as coinitiator decreased the phase separation, but there was a concomitant decrease in mechanical properties. In the neat methacrylate formulations, the maximum rates of free‐radical polymerization with EDMAB or TTMSS were 0.28 or 0.06 s −1, respectively. In the neat silorane resin, the maximum rates of cationic ring‐opening polymerization with EDMAB or TTMSS were 0.056 or 0.087 s −1, respectively. The phase separation phenomenon may be attributed to differences in the rates of free‐radical polymerization of methacrylates and cationic ring‐opening polymerization of silorane. In the hybrid systems, free‐radical polymerization initiated with EDMAB led to higher crosslink density and better mechanical properties under dry/wet conditions. These beneficial effects were, however, associated with an increase in heterogeneity in the network structure. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 841–852, 2016.